Phytochemical Profiling and Wound Healing Activity of Gigantochloa apus Liquid Smoke in Mus Musculus - Tarigan DN; Tarigan YG; Prakasita VC; Prasetyaningsih A; Kachingwe BH (Dove Medical Press, 2024)
Desi Natalia Tarigan,1 Yenni Gustiani Tarigan,2 Vinsa Cantya Prakasita,1 Aniek Prasetyaningsih,1 Baxter HK Kachingwe3 1Faculty of Biotechnology, Duta Wacana Christian University, Yogyakarta, Indonesia; 2Faculty of Pharmacy and Health Sciences, Sari Mutiara Indonesia University, Medan, Indonesia; 3Pharmacy Department, Kamuzu University of Health Sciences, Blantyre, MalawiCorrespondence: Baxter HK Kachingwe, Pharmacy Department, Kamuzu University of Health Sciences, Mahatma Ghandi Road, Private Bag 360, Chichiri, Blantyre, Malawi, Tel +2650994400776, Email bkachingwe@kuhes.ac.mwPurpose: Rope bamboo (Gigantochloa apus) is traditionally used for medicinal purposes, and extracts from stem leaves and shoots have been shown to possess antioxidant and anti-inflammatory activity. Thus, this study looked at the potential compounds present in and the usefulness of Rope bamboo liquid smoke preparations in the wound healing process in mice.Methods: The fingerprinting of the liquid smoke was done by liquid chromatography-mass spectrometry. In-vivo experiments were conducted to observe the diameter and percentage of wound healing in mice for 14 days using topical formulations containing liquid smoke concentrations of 100%, 50%, 25%, positive control and negative control. Statistical analyses were conducted using the Kruskal-Wallis test and Spearman correlation.Results: The phytochemical fingerprint showed the presence of alkaloids, flavonoids, vitamins, phenols, and lipids. The 100% undiluted liquid smoke accelerated wound healing faster compared to 50% and 25% dilutions. The differences in wound diameters were statistically significant across treatments having a p-value of 0.020 and dose-dependent (p = 0.029).Conclusion: Liquid smoke acceleration of the wound healing process was dose-dependent compared to controls. This dose-dependency indicates that the wound healing effects were probably due to the anti-inflammatory, antioxidant, and antimicrobial activities of the elucidated constituents of Rope bamboo liquid smoke. Keywords: dose-dependent, wounds healing, Gigantochloa apus, Rope bamboo, liquid smoke, mice